Republican Support and Economic Hardship: The Enduring Effects of the Opioid Epidemic - Arteaga, Carolina; Barone, Victoria (Quarterly Journal of Economics, 2026)
In this article, we establish a causal connection between two of the most salient social developments in the United States over the past decades: the opioid epidemic and the political realignment between the Republican and Democratic parties. Drawing on unsealed records from litigation against Purdue Pharma, we uncover rich geographic variation in the marketing of prescription opioids that serves as a quasi-exogenous source of exposure to the epidemic. We use this variation to document significant increases in drug-related mortality and greater reliance on public transfer programs. This induced economic hardship led to substantial changes in the political landscape of the communities most affected by the opioid epidemic. We estimate that from the mid-2000s to 2022, exposure to the opioid epidemic continuously increased the Republican vote share in House, presidential, and gubernatorial elections. By the 2022 House elections, a one-standard-deviation increase in our measure of exposure led to a 4.5 percentage point increase in the Republican vote share. From 2012 until 2022, this increase in the House vote share translated into Republicans winning additional seats.